The twin proposal - Thacker, Cathy Gillen (Thacker, Cathy Gillen. Lockharts lost & found., 2021)
"Mackenzie Lockhart just proposed to Griff Montgomery, her secret crush--and best bud since they were kids in foster care. Once the Fort Worth attorney gets his well-deserved promotion, they can return to their independent lives. But when the newlyweds cross the line from friends to lovers, there's no going back. With twins on the way, is this their chance to turn a temporary arrangement into a can't-lose formula for love?"--